خصائص العربية و أسرارها - Yelfi Dewi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2009)
As a part of the language of Samiyah, Arabic has its characteristics that makes it different from other language. Among its Specific features (characteristics), Arabic has phoneme (ashwat), vocabulary (mufradad), syntax (nahwu) and morphology (sharf). In some Arabic words, there are some specialties compared to those of other language that remains the great secret of the Arabic itselfKata Kunci: خصائص، أسرار، العربية